EFFECTS OF MELATONIN AND FLUOXETINE ON OXIDATIVE STRESS PARAMETERS IN STREPTOZOTOCIN-INDUCED DIABETIC RATS (Sciences & Technologie. C, Biotechnologies, 2016)
Chronic hyperglycemia is accompanied by excessive production of free radicals by various mechanisms. This is an indicator of the oxidative stress that is involved in the worsening of chronic complications related to diabetes mellitus. The objective of this study was to evaluate the beneficial effects of melatonin and fluoxetine on diabetes-induced lipid metabolism disorders, as well as on oxidative stress parameters in erythrocytes of diabetic rats following an intraperitoneal injection of streptozotocin (60 mg/kg). It was noted that both treatments exert a regulatory effect on blood glucose and lipid profile parameters, however only melatonin could decrease the lipid peroxidation and improve the antioxidant status in erythrocytes.